2021
DOI: 10.1590/s1677-5538.ibju.2020.0051
|View full text |Cite
|
Sign up to set email alerts
|

Role of salvage lymph node dissection in patients previously treated for prostate cancer: systematic review

Abstract: Prostate cancer is the most common invasive cancer in men. Radical prostatectomy (RP) is a definitive treatment option, but biochemical recurrence can reach 40%. Salvage lymphadenectomy is a relatively recent approach to oligometasis and has been rapidly diffused primarily due to improvement in imaging diagnosis and results showing possibly promising therapy. A systematic literature review was performed in March 2020, according to the PRISMA statement. We excluded studies with patients with suspicion or confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The median number of dissected LNs in our patients (10, interquartile range: 6-25) may be considered relatively low for a good salvage lymphadenectomy. Data from a recent systematic review indicate that other studies on patients undergoing SLND reported median numbers of dissected LNs between 6.5 and 83 [5]. While we reported that having undergone prior radiotherapy was not significantly associated with a reduced number of removed LNs in our patients, contrary to hypothetical expectations that intraoperative difficulties due to post-radiation scarring could have influenced the quality of SLND, having undergone prior extended lymphadenectomy with radical prostatectomy might have been a factor that had influenced the extent of salvage dissection (due to scarring and smaller amounts of remnant lymphatic tissue).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of dissected LNs in our patients (10, interquartile range: 6-25) may be considered relatively low for a good salvage lymphadenectomy. Data from a recent systematic review indicate that other studies on patients undergoing SLND reported median numbers of dissected LNs between 6.5 and 83 [5]. While we reported that having undergone prior radiotherapy was not significantly associated with a reduced number of removed LNs in our patients, contrary to hypothetical expectations that intraoperative difficulties due to post-radiation scarring could have influenced the quality of SLND, having undergone prior extended lymphadenectomy with radical prostatectomy might have been a factor that had influenced the extent of salvage dissection (due to scarring and smaller amounts of remnant lymphatic tissue).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical recurrence (BCR) in prostate cancer (PC) patients managed with curative intent is being commonly encountered in clinical practice, as expected to occur in more than half of men with high-risk disease treated with radical prostatectomy (RP) [1]. In 82-91% of patients with BCR after RP, the location of recurrence is confined to the fossa or pelvic lymph nodes [2], making salvage lymph node dissection (SLND) a reasonable, yet still investigated treatment option in selected patients [3][4][5]. In patients fit for curative salvage treatment, a prostate specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) or choline PET/CT or fluciclovine PET/CT scan is recommended by the contemporary guidelines [6], in order to assess location of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the role of radical prostatectomy and PLND in patients with LNI remains unclear. Some authors argue that surgical treatment improves staging facilitating subsequent multimodal treatments (61) or postpone the onset of systemic therapy (62).…”
Section: What Are the Outcomes Of Radical Prostatectomy And Plnd In N...mentioning
confidence: 99%
“…The removal of pelvic lymph nodes is a important point during the radical prostatectomy and radical cystectomy. The extension of lymph node dissection is controversial and associated with more complications in post-operative period (1). In this interesting paper the topographic anatomy of pelvic compartments in relation to pelvic lymphonodectomy for rectal, uterine, and prostate cancer are reviewed.…”
Section: Commentmentioning
confidence: 99%